2022
DOI: 10.1021/acs.orglett.2c01729
|View full text |Cite
|
Sign up to set email alerts
|

Construction of N-Polyheterocycles by N-Heterocyclic Carbene Catalysis via a Regioselective Intramolecular Radical Addition/Cyclization Cascade

Abstract: N-Polyheterocycles are rapidly accessed by N-heterocyclic carbene (NHC) catalysis through regioselective sequential radical addition/cyclization in the absence of any metals or oxidants. The transformation occurs under mild conditions and enjoys a wide substrate scope with excellent functional group compatibility. Furthermore, a gram-scale synthesis is also conducted. Preliminary mechanistic studies reveal the potential involvement of an NHC radical cation intermediate.N-Polyheterocycles are interesting organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…In 2020, Severin et al reported that stoichiometric amounts of an NHC could donate one electron to the trityl cation . Moreover, we further uncovered a trail of NHC-catalyzed radical coupling reactions , (Scheme a–c) in which the NHC catalyst directly served as a SET reductant for various α-halides, unlike previous reports stemming from Breslow intermediates. As part of our continuous research interest in the construction of diverse heterocycles, , herein we demonstrate a sustainable and redox-neutral route to phenanthridines through NHC-catalyzed intermolecular alkyl radical addition to vinyl azide.…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…In 2020, Severin et al reported that stoichiometric amounts of an NHC could donate one electron to the trityl cation . Moreover, we further uncovered a trail of NHC-catalyzed radical coupling reactions , (Scheme a–c) in which the NHC catalyst directly served as a SET reductant for various α-halides, unlike previous reports stemming from Breslow intermediates. As part of our continuous research interest in the construction of diverse heterocycles, , herein we demonstrate a sustainable and redox-neutral route to phenanthridines through NHC-catalyzed intermolecular alkyl radical addition to vinyl azide.…”
mentioning
confidence: 54%
“…On the basis of preliminary mechanistic investigation and previous literature, , , we proposed a mechanism for this NHC-catalyzed radical process (Scheme ). First, an α-carbon radical B was assumed to be generated in the presence of the NHC catalyst via a SET process. Subsequent radical addition of B to vinyl azide 1a , followed by N 2 extrusion, resulted in the formation of an iminyl radical C .…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In spite of these significant breakthroughs, the transformations mentioned above are overwhelmingly dependent on aldehyde substrates. In this context, we try to expand the substrate compatibility of this Breslow intermediate-based radical chemistry to much wider aldehyde-free functionalities and thereby unlock series of new pathways for the construction of heterocycles (Scheme b) . As part of our consistent effort to develop redox-neutral catalysis and heterocycle construction, we here report the first example of NHC-catalyzed, SOMOphilic isocyanide insertion-initiated HAS (homolytic aromatic substitution)-type radical cyclization, resulting in the facile assembly of structurally functionalized phenanthridine scaffolds (Scheme c), which are quite common in many natural products and pharmaceuticals.…”
mentioning
confidence: 63%